METHODOLOGICAL ASPECTS OF USING MARKETING RESEARCH IN OILCROP GROWING FARMS (Marketing Journal, 2025)
This article examines the methodological aspects of marketing research in oilseed -growing farms. It highlights changes in consumer demand, the growth of the online market, and increased competition, which require modern approaches to marketing activities. The paper discusses main marketing research methods, including consumer studies, market segmentation, and innovation strategies to improve competitiveness. Scientific recommendations are provided for enhancing product assortment and expanding market share.
Keywords: Oilseeds; Farms; Consumers; ASRR (Customer Acquisition; Customer Service; Customer Retention and Customer Return); Marketing Strategies